2014
DOI: 10.14453/aabfj.v8i3.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Independence on the Earnings Quality: Evidence from Portuguese Listed Companies

Abstract: Agency theory suggests that independent outside board members may have an important monitoring function of the financial reporting process. As a result, boards with more independent directors have a tendency for increased monitoring and are therefore expected to insist on better earnings quality. This study examines whether board independence improves earnings quality by reducing earnings management in Portugal, a country with significantly different institutional and legal characteristics from the Anglo-Saxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
2
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 95 publications
6
63
2
25
Order By: Relevance
“…It is believed that a smaller board is able to direct and make better decisions and that a larger board size may lead to less firm performance. Several prior studies document the favorable impact of outside directors on firm decisions aimed at enhancing shareholder wealth (Alves, 2014) but in KSA we can found that all performance measures are insignificantly affected by the independency of board of directors. Overall, the reasons behind insignificant results in Saudi might be as follow: Saudi's listed companies are recently adopted the corporate governance regulations and the effect of those practices are still not have been appears…”
Section: Empirical Studycontrasting
confidence: 61%
“…It is believed that a smaller board is able to direct and make better decisions and that a larger board size may lead to less firm performance. Several prior studies document the favorable impact of outside directors on firm decisions aimed at enhancing shareholder wealth (Alves, 2014) but in KSA we can found that all performance measures are insignificantly affected by the independency of board of directors. Overall, the reasons behind insignificant results in Saudi might be as follow: Saudi's listed companies are recently adopted the corporate governance regulations and the effect of those practices are still not have been appears…”
Section: Empirical Studycontrasting
confidence: 61%
“…Board size refers to the total number of directors on the board of directors of a firm. The importance of board size in influencing firm performance is evidenced by number of empirical studies in recent years (Fuzi, Adliana, & Julizaerma, 2016;Alves, 2014;Hillman & Dalziel, 2003) However, empirical findings have been mixed and inconclusive. A number of issues have ISSN 2330-8362 2017 www.macrothink.org/rbm 2 been attributed with respect to the conflicting findings of past studies.…”
Section: Introductionmentioning
confidence: 99%
“…In short, it is affirmable that past research supports the hypothesis that high percentage of independent outside directors on the board clearly contributes in controlling the practices of earnings management (Alves, 2014). This implies that independent directors cause improvement of the level of earnings quality by reducing the earnings management's level.…”
Section: Board Independencementioning
confidence: 77%